Answer:
x = 0
General Formulas and Concepts:
Pre-Algebra
- Order of Operations: BPEMDAS
- Equality Properties
Explanation:
Step 1: Define equation
5x - 8(1 + 7x) = -8
Step 2: Solve for x
- Distribute -8: 5x - 8 - 56x = -8
- Combine like terms: -51x - 8 = -8
- Isolate x term: -51x = 0
- Isolate x: x = 0
Step 3: Check
Plug in x into the original equation to verify it is a solution.
- Substitute in x: 5(0) - 8(1 + 7(0)) = -8
- Multiply: 0 - 8(1 + 0) = -8
- Add: -8(1) = -8
- Multiply: -8 = -8
Here we see that -8 does indeed equal -8.
∴ x = 0 is a solution of the equation.